Performance comparisons of two flat-plate photovoltaic thermal collectors with different channel configurations. (15th May 2019) - Yu, Y.; Yang, H.; Peng, J.; Long, E.
Abstract: A performance study with experiments and TRNSYS simulations was conducted for two water-type roll-bond photovoltaic thermal (PVT) collectors installed in Chengdu, Sichuan, western China. The two PVT collectors differed in absorber plate configurations, one with a conventional harp-channel configuration and the other with a novel grid-channel arrangement. The results of the experiments demonstrated that the grid-channel PVT collector had higher thermal and PV power efficiencies than those of the harp-channel collector while the harp-channel PVT collector had much lower water flow pressure drop than that of the grid-channel PVT collector. TRNSYS models for the parallel-tube PVT collectors were seamlessly applied to the harp-channel roll-bond PVT collector with some input parameters altered, which could also be applicable to the grid-channel PVT collector with the property parameter derived from test data. Moreover, the annual energy production of the two PVT-DHW (domestic hot water) systems were simulated and compared for three different cities of Sichuan Province. This study lays the foundation for the performance simulation and optimization of the proposed PVT systems for applications in the western rural area of China. Highlights: A PVT collector with the grid-channel absorber is designed for rural residence. The performance of the novel PVT collector is compared with the conventional one. The PVT can be simulated by TRNSYS with the parameter derived from test data. The simulation method can be applicable to PVTs with any channel configurations.